On functions with monotonic differences - Rajba, Teresa (Annales Mathematicae Silesianae, 2024)
Motivated by the Szostok problem on functions with monotonic differences (2005, 2007), we consider a-Wright convex functions as a generalization of Wright convex functions. An application of these results to obtain new proofs of known results as well as new results is presented.